Cloud Based Secure Storage for Online Examination System - A.R.Gadekar, Mr; M.V.Sarode, Dr; V.M.Thakare, Dr (International Journal of Engineering and Technology, 2018)
As there has been a vast advancement in information and communication technology, there is a need for change in traditional examination system. Traditional examination system is to be replaced by online examination system. A cloud based solution is proposed to tackle the various issues in educational institutions. Here, we propose architecture for an android based examination system using cloud computing concept. In this we attempt to show an applicability, usage of cloud storage in examination management in education. Android is used to simplify the tasks. The thumb verification device is used to authenticate the user. Some encryption techniques are used for providing security to data.Â Â